A systematic and bibliometric analysis on 3D printing published in scientiﬁc citation index-expanded indexed journals between 1999 and 2019 - Muhammad, Aisha; Ali, Mohammed A. H.; Shanono, Ibrahim Haruna; Abdullah, Nor Rul Hasma (Elsevier Ltd, 2021)
Recently, there has been a rapid increase in the use of additive manufacturing technologies in different sectors. Approaches of additive production (AM) have actually been created to fulfil the need of printing complicated frameworks at great resolutions. Rapid prototyping, the capability to print huge frameworks, decreasing printing problems and also improving mechanical properties are a few of the vital elements that have actually driven the advancement of AM innovations. Additive production has actually been extensively used in various markets, consisting of building, prototyping and also biomechanical. The uptake of 3D printing in the building and construction sector, particularly, was restricted as well as extremely sluggish regardless of the benefit. This paper intends to give review of the major 3D printing methods used in present state as well as applications in different sectors. The paper also presents bibliometric review on the published articles between 1999 and 2019 to as a stepping stone to interested researchers wishing to publish their work in 3D printing.